Mehrsprachigkeit in transmodaler Kommunikation: Praktiken der Sprachalternation in deutsch-arabischen WhatsApp-Chats - König, Katharina (Linguistik Online, 2021)
The paper is concerned with codeswitching in transmodal WhatsApp messenger chats. Based on a corpus of text and audio postings from a group of German-Lebanese cousins that is complemented by ethnographic interviews, the study shows that language alternations can be associated with particular metapragmatic or indexical functions in the different modalities. In audio postings, switching between German and Arabic contextualises varying discourse relations. Also, the cousins use Arabic discourse markers (such as ya’ne, ‘it means’) frequently to structure their talk. In contrast, when they switch to Arabic in their text-postings – using Arabizi, a CMC-register in the Arabic-speaking world – this recurrently establishes a playful or ironic frame for ritual teasings. The final section discusses these transmodal and multilingual practices as multi-layered identity positionings vis-à-vis a monolingual society, their multilingual family and networked communities.